2017
DOI: 10.1021/acs.jnatprod.6b00872
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the Phenolic Compounds of the Four Major Seed Coat Types and Their Relation to Color Genes in Lentil

Abstract: Phenolic compounds can provide antioxidant health benefits for humans, and foods such as lentils can be valuable dietary sources of different subclasses of these secondary metabolites. This study used LC-MS analyses to compare the phenolic profiles of lentil genotypes with four seed coat background colors (green, gray, tan, and brown) and two cotyledon colors (red and yellow) grown at two locations. The mean area ratio per mg sample (MARS) values of various phenolic compounds in lentil seeds varied with the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 30 publications
3
37
0
Order By: Relevance
“…Similar to this study, Mirali et al (2017) reported fewer phenolic compounds in lentil cotyledons compared with whole seeds. Various studies have reported a differential pattern of polyphenol distribution in seed coats and cotyledons.…”
Section: Variation In Polyphenol Type and Concentration In Seed Coatssupporting
confidence: 88%
See 2 more Smart Citations
“…Similar to this study, Mirali et al (2017) reported fewer phenolic compounds in lentil cotyledons compared with whole seeds. Various studies have reported a differential pattern of polyphenol distribution in seed coats and cotyledons.…”
Section: Variation In Polyphenol Type and Concentration In Seed Coatssupporting
confidence: 88%
“…The phenolic compounds and the six isotopically labeled internal standards used in this study are listed in Table 2, along with their supplier information. Different classes of the phenolic compounds including subclasses of phenolic acids, stilbenes, anthocyanidins, flavan-3-ols, proanthocyanidins, flavanones, flavones, dihydroflavonols, and flavonols analyzed in this study were previously quantified in lentils (Mirali et al, 2016(Mirali et al, , 2017. Catechin-13 C 3 , 4-hydroxybenzoic acid-13 C 7 , ferulic acid-d 3 , resveratrol (4-hydroxyphenyl-13 C 6 ), vanillin ring-13 C 6 , and quercetin-d 3 were used as internal standards.…”
Section: Reagents and Standardsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, polyphenols in pulse seed coat extracts were analysed with absolute quantification, instead of relative quantification used in previous work . Calibration curves for each analyte were generated from injections of the five standards (concentrations in Table S1) at the beginning and end of the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The polyphenol profiles of seed coats with different colours within a pulse crop, or among pulse crops, are diverse . In order to effectively use pulse seed coats, characterisation and quantification of their polyphenols is needed, which requires a robust, sensitive, and selective method.…”
Section: Introductionmentioning
confidence: 99%